Waters Signatures with Optimal Security Reduction - Hofheinz, Dennis; Jager, Tibor; Knapp, Edward (Public Key Cryptography - PKC 2012 - 15th International Conference on Practice and Theory in Public Key Cryptography, Darmstadt, Germany, May 21-23, 2012. Proceedings)

Proving Linearizability of Multiset with Local Proof Obligations - Travkin, Oleg; Wehrheim, Heike; Schellhorn, Gerhard (ECEASST)

Model evolution and refinement - Ruhroth, Thomas; Wehrheim, Heike (Sci. Comput. Program.)

How to Prove Algorithms Linearisable - Schellhorn, Gerhard; Wehrheim, Heike; Derrick, John (Computer Aided Verification - 24th International Conference, CAV 2012, Berkeley, CA, USA, July 7-13, 2012 Proceedings)

Long term higher urinary calcium excretion within the normal physiologic range predicts impaired bone status of the proximal radius in healthy children with higher potential renal acid load - Shi, Lijie; Libuda, Lars; Schönau, Eckhard; Frassetto, Lynda; Remer, Thomas (Bone)

Dietary fatty acid intake, its food sources and determinants in European adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. - Vyncke, KE; Libuda, Lars; De Vriendt, T; Moreno, LA; Van Winckel, M; Manios, Y; Gottrand, F; Molnar, D; Vanaelst, B; Sjöström, M; González-Gross, M; Censi, L; et al. (Br J Nutr)

Beverage consumption among European adolescents in the HELENA study. - Duffey, KJ; Huybrechts, I; Mouratidou, T; Libuda, Lars; Kersting, M; De Vriendt, T; Gottrand, F; Widhalm, K; Dallongeville, J; Hallström, L; González-Gross, M; De Henauw, S; et al. (Eur J Clin Nutr)

Computer science and society as a field of computer science - Engbring, Dieter; Selke, Harald
In this article we report on the experiences of a redesigned teaching in the field of computer science and society (IuG). The reasons for the redesign and the concept are outlined. We have condensed our experiences into theses: 1. Computer science and society should be a compulsory course in the bachelor's degree, in which students get an overview of which social framework conditions are relevant for them and how they can be incorporated into practice. 2. Historical contents of computer science are to be processed here by considering current developments in the context of their genesis.

User Centered Design of an Interactive Mobile Assistance and Supervision System for Rehabilitation Purposes - Klompmaker, Florian; Workowski, Anke; Thronicke, Wolfgang; Ostermair, Florian; Willemsen, Detlev; Hoffmann, D

Towards Multimodal 3D Tabletop Interaction using Sensor Equipped Mobile Devices - Klompmaker, Florian; Nebe, Karsten; Eschenlohr, Julien

The technical potential of digital boards - Selke, Harald; Winkelnkemper, Felix
This article explains the technical potential of digital boards with which more and more schools are being equipped. A consideration of current usage scenarios of these interactive whiteboards shows that a large part of this potential is still unused and the deficits of the software often have to be circumvented with tricks, especially for use in demanding, student-oriented lessons. Finally, the further development of existing teaching scenarios using this technical potential shows that considering the technical possibilities of digital boards can motivate new didactic scenarios.

Der Qualitätsstandard für Usability Engineering der German UPA - Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut

Base Requirements for Virtual Tabletop Groupware Artifacts - Tobias, Müller; Nebe, Karsten; Klompmaker, Florian

Collaborative work on interactive displays - design, operation and fields of application - Fischer, Holger Gerhard; Klompmaker, Florian (M & C, humans and computers)

Das Heinz Nixdorf Institut: Über 25 Jahre interdisziplinär erfolgreich - Keil, Reinhard

EVALUATION OF WHOLE-BODY NAVIGATION AND SELECTION TECHNIQUES IN IMMERSIVE 3D ENVIRONMENTS - Klompmaker, Florian; Dridger, Alexander; Nebe, Karsten (Proceedings of the ASME 2012 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)
Since 2010 when the Microsoft Kinect with its integrated depth-sensing camera appeared on the market, completely new kinds of interaction techniques have been integrated into console games. They don’t require any instrumentalization and no complicated calibration or time-consuming setup anymore. But even having these benefits, some drawbacks exist. Most games only enable the user to fulfill very simple gestures like waving, jumping or stooping, which is not the natural behavior of a user. In addition the depth-sensing technology lacks of haptic feedback. Of course we cannot solve the lack of haptic feedback, but we want to improve the whole-body interaction. Our goal is to develop 3D interaction techniques that give a maximum of freedom to the user and enable her to perform precise and immersive interactions. This work focuses on whole-body interaction in immersive virtual environments. We present 3D interaction techniques that provide the user with a maximum of freedom and enables her to operate precisely and immersive in virtual environments. Furthermore we present a user study, in which we analyzed how Navigation and Manipulation techniques can be performed by users’ body-interaction using a depth-sensing camera and a huge projection screen. Therefore three alternative approaches have been developed and tested: classical gamepad interaction, an indirect pointer-based interaction and a more direct whole- body interaction technique. We compared their effectiveness and preciseness. It turned out that users act faster, while using the gamepad, but generate significantly more errors at the same time. Using depth-sensing based whole-body interaction techniques it became apparent, that the interaction is much more immersive, natural and intuitive, even if slower. We will show the advantages of our approach and how it can be used in various domains, more effectively and efficiently for their users.

Integrating Usability Engineering in the Software Development Lifecycle Based on International Standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS), Copenhagen, Denmark)

Durchl {\ "a} ssigkeitsorientierte Bildung - Keil, Reinhard; Niehus, Dominik; Ossenschmidt, Daniel

Automatic emotion recognition - technologies, interpretation and applications - Brand, Marcel; Klompmaker, Florian; Schleining, Peter; Weiss, Fabian (Computer science spectrum)

Enriching Disaster Control Management based on Human-Centered Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM), Vancouver, Kanada)